Negative electrode material and battery
By introducing organic polymers and metal elements on the surface and inside of the graphite, forming composites and adjusting the pore volume ratio, the problem of poor electrochemical performance of traditional graphite negative electrode materials is solved, and the first Coulomb efficiency and cycle of lithium-ion batteries is improved performance.
Patent Information
- Application Number
- CN202411367524.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Traditional graphite negative electrode materials have irreversible side reactions caused by many surface defects, poor electrolyte compatibility and high specific surface area in lithium-ion batteries, which affect their electrochemical performance and are difficult to achieve precise regulation of pore volume, resulting in the first Coulomb efficiency and cycle. Poor performance.
By forming organic polymer materials on the surface and/or inside the graphite, and introducing metal elements such as lithium, sodium, potassium, aluminum, form an inorganic-organic composite similar to a metal-organic frame material, fill or cover the pore portions, adjust the pore size The proportion of pore volume in the range of 5nm to 35nm reduces the direct contact between lithium ions and graphite, and enhances electrical conductivity and interface stability.
It improves lithium ion transport dynamics, improves the first Coulomb efficiency and cycle stability of the negative electrode material, reduces irreversible side reactions, and achieves better electrochemical performance.
Smart Images

Figure CN119275264A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials, and in particular, to negative electrode materials and batteries. Background Art
[0002] The rapid development of lithium-ion batteries has brought about rapid changes in human life. As one of the core components of lithium-ion batteries, negative electrode materials have a significant impact on the electrochemical performance of lithium-ion batteries. Therefore, the development of cost-effective negative electrode materials is of great significance in lithium-ion battery research. Graphite materials are widely used negative electrode materials for lithium-ion batteries, but traditional graphite materials still have many surface defects and poor electrolyte compatibility. The high specific surface area of graphite materials leads to serious irreversible side reactions at the material interface during charging and discharging, resulting in low initial Coulomb efficiency of the material and continuous decay of cycle capacity, which seriously hinders the further application of graphite negative electrode materials.
[0003] At present, the industry mainly uses surface coating to modify graphite to reduce direct contact between electrolyte and natural graphite and reduce the occurrence of side reactions. However, it is difficult to achieve precise control of pore volume for conventional asphalt-coated graphite materials, and the lithium ion transmission capacity of the negative electrode material after surface coating decreases, resulting in a decrease in the initial efficiency of graphite materials. Summary of the invention
[0004] In view of this, the present application provides a negative electrode material and a battery, wherein the negative electrode material can comprehensively improve lithium ion transfer kinetics, first coulombic efficiency and cycle performance.
[0005] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising graphite and an organic polymer material located on the surface and / or inside of the graphite;
[0006] The negative electrode material comprises a metal element, wherein the metal element comprises at least one of lithium, sodium, potassium and aluminum; based on the total mass of the negative electrode material being 100%, the mass content of the metal element is 1300ppm to 4400ppm;
[0007] The negative electrode material has pores, wherein the volume proportion of pores with a pore diameter ranging from 5 nm to 35 nm in the total pore volume is 15% to 30%.
[0008] In some embodiments, the volume of pores with a pore diameter of less than 5 nm in the negative electrode material accounts for 2% to 10% of the total pore volume.
[0009] In some embodiments, the volume of pores with a pore diameter of 35 nm or more in the negative electrode material accounts for 60% to 83% of the total pore volume.
[0010] In some embodiments, the total pore volume of pores with a pore size of less than 250 nm in the negative electrode material is 0.005 cm 3 / g~0.02cm 3 / g.
[0011] In some embodiments, the organic polymer material on the graphite surface forms a coating layer, and the thickness of the coating layer is 20 nm to 200 nm.
[0012] In some embodiments, the graphite includes at least one of artificial graphite, natural graphite, and microcrystalline graphite.
[0013] In some embodiments, the fixed carbon content of the graphite is ≥ 98%.
[0014] In some embodiments, the negative electrode material comprises a non-metallic element, and the non-metallic element includes at least one of nitrogen, sulfur, oxygen, boron and fluorine.
[0015] In some embodiments, the median particle size of the negative electrode material is 3 μm to 25 μm.
[0016] In some embodiments, the negative electrode material has a powder conductivity of ≤1.35*10 2 S / cm.
[0017] In some embodiments, the specific surface area of the negative electrode material is 1.2 m 2 / g~3.7m 2 / g.
[0018] In some embodiments, the tap density of the negative electrode material is 1.0 g / cm 3 ~1.3g / cm 3 .
[0019] In some embodiments, in the Raman test spectrum of the negative electrode material, the negative electrode material has a -1 -1400cm -1 There is a D peak at 1550cm -1 -1600cm -1 There is a G peak between them, and the Raman area ratio of the D peak to the G peak is I D / I G ≤0.40.
[0020] The present application provides a battery, which includes the above-mentioned negative electrode material.
[0021] The technical solution of this application has at least the following beneficial effects:
[0022] The negative electrode material provided by the present application forms an organic polymer material on the surface and / or inside of graphite, and the negative electrode material contains metal elements, and the metal elements include at least one of lithium, sodium, potassium, and aluminum elements. The total content of the metal elements is in the range of 1300ppm-4400ppm. The presence of the metal elements can not only enhance the conductivity within the graphite particles and / or between the graphite particles, promote the interface transmission of lithium ions, and improve the first coulombic efficiency and cycle stability of the negative electrode material. At the same time, some metal elements can also generate inorganic-organic composites similar to metal-organic framework materials with organic polymer materials. The inorganic-organic composite can be filled in the graphite and / or attached to the surface of the graphite particles, thereby adjusting the volume proportion of pores with a pore size in the range of 5nm to 35nm in the total pore volume to 15% to 30%. The pores on the surface and / or inside of the graphite are partially filled or covered, which can effectively reduce the direct contact area between the solvated lithium ions and the graphite, reduce the irreversible side reactions between the negative electrode material and the electrolyte, enhance the stability of the solid-liquid contact interface of the negative electrode material, and improve the first coulombic efficiency of the negative electrode material. Therefore, the present application simultaneously controls the mass content of metal elements and the pore volume ratio, which can improve the lithium ion transfer kinetics and enable the negative electrode material to have both better first coulombic efficiency and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A process flow chart of the preparation method of the negative electrode material provided in this application;
[0024] Figure 2 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application;
[0025] Figure 3a and Figure 3b They are electron microscope images of the negative electrode material prepared in Example 1 of the present application at different magnifications;
[0026] Figure 4a This is a pore size distribution diagram of the negative electrode material prepared in Example 1 of the present application in the range of 5nm to 35nm;
[0027] Figure 4b This is a distribution diagram of pore sizes below 160 nm in the negative electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0028] In order to better illustrate the present application and facilitate understanding of the technical solution of the present application, the present application is further described in detail below. However, the following embodiments are only simple examples of the present application and do not represent or limit the scope of protection of the present application. The scope of protection of the present application shall be subject to the claims.
[0029] Based on this, in a first aspect, the present application provides a negative electrode material, the negative electrode material comprising graphite and an organic polymer material located on the surface and / or inside of the graphite;
[0030] The negative electrode material contains a metal element, and the metal element includes at least one of lithium, sodium, potassium and aluminum; based on the total mass of the negative electrode material being 100%, the mass content of the metal element is 1300ppm to 4400ppm;
[0031] The negative electrode material has pores, wherein the volume proportion of pores with a pore diameter ranging from 5 nm to 35 nm in the total pore volume is 15% to 30%.
[0032] The negative electrode material provided by the present application forms an organic polymer material on the surface and / or inside of graphite, and the negative electrode material contains metal elements, and the metal elements include at least one of lithium, sodium, potassium, and aluminum elements. The total content of the metal elements is in the range of 1300ppm-4400ppm. The presence of the metal elements can not only enhance the conductivity within the graphite particles and / or between the graphite particles, promote the interface transmission of lithium ions, and improve the first coulombic efficiency and cycle stability of the negative electrode material. At the same time, some metal elements can also generate inorganic-organic composites similar to metal-organic framework materials with organic polymer materials. The inorganic-organic composite can be filled in the graphite and / or attached to the surface of the graphite particles, thereby adjusting the volume proportion of pores with a pore size in the range of 5nm to 35nm in the total pore volume to 15% to 30%. The pores on the surface and / or inside of the graphite are partially filled or covered, which can effectively reduce the direct contact area between the solvated lithium ions and the graphite, reduce the irreversible side reactions between the negative electrode material and the electrolyte, enhance the stability of the solid-liquid contact interface of the negative electrode material, and improve the first coulombic efficiency of the negative electrode material. Therefore, the present application simultaneously controls the mass content of metal elements and the pore volume ratio, which can improve the lithium ion transfer kinetics and enable the negative electrode material to have both better first coulombic efficiency and cycle performance.
[0033] In some embodiments, the total mass of the negative electrode material is 100%, and the mass content of the metal element obtained by inductively coupled plasma testing is 1300ppm to 4400ppm, which can be specifically 1300ppm, 1500ppm, 1700ppm, 1900ppm, 2000ppm, 2300ppm, 2500ppm, 2800ppm, 3000ppm, 3500ppm, 4000ppm or 4400ppm, etc., and of course, it can also be other values within the above range, which is not limited here. When the total content of metal elements in the negative electrode material is less than 1300ppm, the interfacial lithium ion transmission of the negative electrode material is slow, which is not conducive to the performance of the capacity of the negative electrode material; at the same time, it will cause the pH value of the negative electrode material to be low, and the difficulty of electrode processing will increase; when the total content of metal elements in the negative electrode material is greater than 4400ppm, the inorganic-organic complex in the negative electrode material increases, so that the specific surface area of the negative electrode material increases, the side reaction between the negative electrode material and the electrolyte is aggravated, and the first coulomb efficiency of the negative electrode material is reduced.
[0034] In some embodiments, the volume proportion of pores with a pore size in the range of 5nm to 35nm in the total pore volume is 15% to 30%, which can be specifically 15%, 18%, 20%, 22%, 25%, 28% or 30%, etc., and of course it can also be other values within the above range, which are not limited here. In the present application, the volume proportion of pores with a pore size in the range of 5nm to 35nm in the total pore volume is controlled to be 15% to 30%, which can ensure that the contact area between the solvated lithium ions in the electrolyte and the negative electrode material is moderate, which is conducive to the electrolyte fully infiltrating the negative electrode material, which is conducive to improving the lithium ion transmission efficiency and improving the capacity of the negative electrode material; at the same time, it can reduce the consumption of irreversible lithium ions in the first lithium insertion process and improve the first coulombic efficiency of the negative electrode material. When the volume proportion of pores with a pore size in the range of 5nm to 35nm in the total pore volume is less than 15%, the contact area between the solvated lithium ions in the electrolyte and the negative electrode material is too small, and the electrolyte is difficult to fully infiltrate the negative electrode material, resulting in the obstruction of lithium ion transmission and the obstruction of lithium ion transmission kinetics, affecting the capacity of the negative electrode material. When the volume proportion of pores with a pore size in the range of 5nm to 35nm in the total pore volume is greater than 30%, the contact area between the solvated lithium ions in the electrolyte and the negative electrode material is too large, resulting in the aggravation of the irreversible side reaction of the first lithium insertion, excessive consumption of active lithium ions, and a decrease in the first coulombic efficiency of the negative electrode material.
[0035] In some embodiments, in some embodiments, the volume proportion of pores with a pore diameter of less than 5 nm in the negative electrode material in the total pore volume is 2% to 10%, specifically 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., and of course it can also be other values within the above range, which is not limited here.
[0036] In some embodiments, the volume proportion of pores with a pore diameter of more than 35 nm in the negative electrode material in the total pore volume is 60% to 83%, specifically 60%, 63%, 65%, 68%, 70%, 75%, 78%, 80% or 83%, etc., and of course it can also be other values within the above range, which is not limited here.
[0037] In some embodiments, the total pore volume of pores with a pore size of less than 250 nm in the negative electrode material is 0.005 cm 3 / g~0.02cm 3 / g, specifically 0.005cm 3 / g, 0.008cm 3 / g, 0.01cm 3 / g, 0.012cm 3 / g, 0.015cm 3 / g, 0.018cm 3 / g or 0.02cm 3 / g, etc., and can certainly be other values within the above range, which are not limited here.
[0038] In some embodiments, the graphite includes at least one of artificial graphite, natural graphite and microcrystalline graphite. Natural graphite is flake graphite, which is natural phaneritic graphite. It is shaped like fish phosphate, belongs to the hexagonal system, has a layered structure, and has good properties such as high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, and acid and alkali resistance. Artificial graphite is a graphite material obtained by carbonizing organic matter and then subjecting it to high-temperature graphitization treatment.
[0039] In some embodiments, the graphite includes spherical graphite, which is natural graphite.
[0040] In some embodiments, the fixed carbon content of the graphite is ≥ 98%, specifically 98%, 98.2%, 98.3%, 98.8%, 99%, 99.2% or 99.5%, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. Preferably, the fixed carbon content of the graphite is ≥ 99%.
[0041] In some embodiments, the organic polymer material on the graphite surface forms a coating layer, and the thickness of the coating layer is 20nm to 200nm. Specifically, it can be 20nm, 50nm, 80nm, 110nm, 140nm, 170nm or 200nm, but it is not limited to the listed values. Other values not listed in the numerical range are also applicable. Preferably, the coating layer thickness is 40nm to 100nm.
[0042] In some embodiments, the specific surface area of the negative electrode material is 1.2 m 2 / g~3.7m 2 / g; specifically, it can be 1.2m 2 / g, 1.5m 2 / g, 1.9m 2 / g, 2.1m 2 / g, 2.6m 2 / g, 2.9m 2 / g, 3.1m 2 / g, 3.3m 2 / g, 3.5m 2 / g or 3.7m 2 / g, of course, it can also be other numbers within the above range, which is not limited here. When the specific surface area of the negative electrode material is controlled within the above range, the side reaction between the negative electrode material and the electrolyte is reduced, which is conducive to improving the first coulombic efficiency of the negative electrode material.
[0043] In some embodiments, the median particle size of the negative electrode material is 3 μm to 25 μm; more specifically, it can be 3 μm, 4 μm, 6 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 17 μm, 20 μm, 22 μm or 25 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In some embodiments, the negative electrode material has a powder conductivity of ≤1.35*10 2 S / cm, more specifically, can be 1.35*10 2 S / cm, 1.15*10 2 S / cm, 0.95*10 2 S / cm, 0.75*10 2 S / cm or 0.55*10 2 S / cm, etc., but are not limited to the listed values, and other values not listed in this range are also applicable. The lower the powder conductivity of the negative electrode material, the denser the generated coating layer, the more stable the corresponding interface layer, which is beneficial to the first coulombic efficiency and cycle stability of the negative electrode material.
[0045] In some embodiments, in the Raman test spectrum of the negative electrode material, the negative electrode material has a wavelength of 1300 cm -1 -1400cm -1 There is a D peak at 1550cm -1 -1600cm -1 There is a G peak between them, and the Raman area ratio of the D peak to the G peak is I D / I G ≤0.40. D / I GSpecifically, it can be 0.40, 0.35, 0.30, 0.25, 0.20, 0.15 or 0.10, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. Preferably, I D / I G ≤0.35.
[0046] In a second aspect, the present application provides a method for preparing a negative electrode material, such as Figure 1 As shown, the following steps are included:
[0047] Step S10, mixing graphite with an organic coating solution of a coating material having active groups to obtain a mixed solution, wherein the mass ratio of graphite to the coating material is 100:(1-6).
[0048] Step S20, the mixed solution is polymerized under stirring to deposit the coating material on the surface of the graphite material; a pH regulator containing metal ions is added to adjust the pH of the mixed solution to neutral, and the stirring process is continued to obtain a negative electrode material slurry;
[0049] Step S30, performing solid-liquid separation on the negative electrode material slurry and drying to obtain the negative electrode material.
[0050] In the above scheme, graphite is mixed with an organic coating solution so that part of the coating material can be polymerized and deposited on the graphite surface, and then a pH regulator containing metal ions is added to adjust the pH value of the mixed solution. At the same time, the metal ions in the pH regulator can be doped into the polymer to form an organic-inorganic composite. The inorganic-organic composite can be filled inside the graphite and / or attached to the surface of the graphite particles, thereby adjusting the volume proportion of pores with a pore size in the range of 5nm to 35nm in the negative electrode material in the total pore volume. The polymer and the inorganic-organic composite jointly form a coating layer on the graphite surface, so that the pores on the graphite surface and / or inside are partially filled or covered, which can effectively reduce the direct contact area between the solvated lithium ions and the graphite, reduce the irreversible side reactions between the negative electrode material and the electrolyte, and the solid-liquid contact interface of the negative electrode material is stable, thereby improving the first coulomb efficiency of the negative electrode material.
[0051] The following is a detailed description of the preparation method provided in this scheme:
[0052] Step S10, mixing graphite with an organic coating solution of a coating material having active groups to obtain a mixed solution, wherein the mass ratio of graphite to the coating material is 100:(1-6).
[0053] In some embodiments, the active group includes at least one of a sulfonic acid group, a carbonyl group, a carboxyl group, a hydroxyl group, a fluorine-containing group, a boron-containing group, and an amine group.
[0054] In some embodiments, the coating material having an active group includes at least one of sodium sulfamate, ammonium sulfamate, hydroxyethyl sulfonic acid, sulfamic acid, benzenesulfonic acid, aminobenzenesulfonic acid, hydroxybenzenesulfonic acid, vinylsulfonic acid, ethanesulfonic acid, hydroxyurea, hydroxythiobenzamide, hydroxybenzoic acid, aminouracil, aminofluorophenol, salicylic acid, acetylsalicylic acid, aminosalicylic acid, p-aminosalicylic acid, methylsalicylic acid, benzenesulfonamide, acetylethanolamine, vinylamine, benzoic acid, fluorobenzoic acid, tetrafluoroterephthalic acid, acetylbenzoic acid, vinylbenzoic acid, fluorinated vinyl, boric acid, fluoroboric acid, and nitrobenzoic acid.
[0055] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite. Natural graphite is flake graphite, which is natural phaneritic graphite. It is shaped like fish phosphate, belongs to the hexagonal system, has a layered structure, and has good properties such as high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, and acid and alkali resistance. Artificial graphite is a graphite material obtained by carbonizing organic matter and then subjecting it to high-temperature graphitization treatment.
[0056] Understandably, defects will be formed in graphite during the process of spheroidization and purification, and the defects have high reactivity due to unsaturated chemical bonds. A coating material with active groups and graphite are dispersed in a solvent to form a mixed solution. In the mixed solution, the highly reactive sites on the graphite surface react chemically with the active groups in the coating material, and polymerization reactions also occur between the coating material molecules to form a continuous coating film layer, which reduces the defect density of the graphite material.
[0057] In some embodiments, the graphite includes spherical graphite, which is natural graphite.
[0058] In some embodiments, the median particle size of the graphite is 3 μm to 25 μm, more specifically, 3 μm, 5 μm, 8 μm, 10 μm, 11 μm, 13 μm, 16 μm, 18 μm, 20 μm, 23 μm or 25 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The control of the median particle size of the graphite within the above range is conducive to reducing the specific surface area, reducing the contact between the graphite and the electrolyte, and inhibiting the occurrence of side reactions.
[0059] In some embodiments, the fixed carbon content in the graphite is ≥ 98%, specifically 98%, 98.3%, 98.5%, 98.6%, 98.8%, 99.2% or 99.5%, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. Preferably, the fixed carbon content in the graphite is ≥ 99%.
[0060] In some embodiments, the organic coating solution further comprises a solvent, and the solvent includes but is not limited to at least one of water, ethanol, methanol, benzene, acetone, N-methylpyrrolidone, and NN-dimethylformamide.
[0061] In some embodiments, in the organic coating solution, the solid-liquid ratio of the coating material to the solvent is 1:(20-1000), specifically 1:20, 1:40, 1:80, 1:100, 1:200, 1:500, 1:800 or 1:1000, etc., which are not limited here. When the solid-liquid ratio of the coating material to the solvent is too high, the concentration of the coating material per unit volume of the organic coating solution is too high, and too much coating material is prone to agglomeration. The agglomerates are deposited on the surface of the graphite material, making it difficult to effectively fill the pores in the graphite material. An overly thick coating layer will also aggravate the obstruction of the lithium ion transmission channel of the negative electrode material, which is not conducive to the performance of the negative electrode material. When the solid-liquid ratio of the coating material to the solvent is too low, the amount of solvent required for material preparation increases, and the production cost increases.
[0062] In some embodiments, the mass ratio of graphite to coating material is 100:(1-6), which can be 100:1, 100:2, 100:3, 100:4, 100:5 or 100:6, etc., which are not limited here. Too much coating material leads to a too thick coating layer on the surface of graphite, and the pore volume ratio of 5nm to 35nm decreases, resulting in a small direct contact area between the solvated lithium ions in the electrolyte and the graphite, and the negative electrode material Li + The transmission kinetics are poor, and the first-cycle lithium removal capacity of the negative electrode material decreases. Too little coating material leads to a decrease in the uniformity of the coating layer on the graphite surface, an increase in the pore volume ratio in the 5nm-35nm range, and an excessively large direct contact area between the solvated lithium ions in the electrolyte and the graphite, which leads to an increase in the irreversible side reaction of the first lithium insertion, excessive consumption of active lithium ions, and a decrease in the first coulombic efficiency of the negative electrode material.
[0063] Step S20, the mixed solution is polymerized under stirring to deposit the coating material on the surface of the graphite material; a pH regulator containing metal ions is added to adjust the pH of the mixed solution to neutral, and the stirring process is continued to obtain a negative electrode material slurry.
[0064] In some embodiments, the polymerization temperature is 40°C to 80°C, and the holding time is 0.5h to 6h. Specifically, the polymerization temperature is 40°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and the holding time can be 0.5h, 0.8h, 1h, 4h, 5h or 6h.
[0065] In some embodiments, the polymerization reaction is carried out under stirring, and the polymer formed by the polymerization of the coating material having active groups is deposited and attached to the surface of the graphite.
[0066] In some embodiments, the pH value of the polymerization reaction is controlled at 6.5-7.5, specifically 6.5, 6.6, 6.7, 6.8, 6.9, 7, 7.1, 7.2, 7.3 or 7.5, etc., and may be other values within the above range, which is not limited here.
[0067] In some embodiments, the pH adjuster containing metal ions includes, but is not limited to, at least one of sodium hydroxide, sodium carbonate, lithium hydroxide, lithium carbonate, potassium hydroxide, and aluminum oxide.
[0068] In some embodiments, the molar ratio of the metal ion-containing pH adjuster to the coating material is 1:(0.8-2.2), specifically 1:0.8, 1:0.9, 1:1.1, 1:1.3, 1:1.5, 1:1.8, 1:1.9 or 1:2.2, etc., and of course it can also be other values within the above range, which is not limited here. When the addition ratio of the pH adjuster containing metal ions is too low, it is difficult for the metal ions in the coating material and the coating material to form a complex similar to the metal-organic framework material, and it is difficult to accurately adjust the pore volume proportion of the negative electrode material in the range of 5nm to 35nm, resulting in an increase in the pore volume proportion of the negative electrode material in the range of 5nm to 35nm, an increase in the direct contact area between the solvated lithium ions and the graphite material, and a deterioration in the electrochemical performance; when the addition ratio of the pH adjuster containing metal ions is too high, the pH adjuster in the mixed solution undergoes a self-deposition reaction, resulting in the appearance of inorganic agglomerates on the originally uniform coating layer, causing the specific surface area of the negative electrode material to increase. At the same time, the pore volume proportion of the negative electrode material in the range of 5nm to 35nm also increases, and the inorganic agglomerates do not have lithium storage activity, which will further lead to a decrease in the capacity of the negative electrode material.
[0069] Step S30, performing solid-liquid separation on the negative electrode material slurry and drying to obtain the negative electrode material.
[0070] In some embodiments, the solid-liquid separation is at least one of stirring volatilization, spray separation, and rake stirring separation.
[0071] In some embodiments, the drying process is at least one of air drying, vacuum drying, flash drying, freeze drying, spray drying, and the like.
[0072] In some embodiments, the drying temperature is 110°C to 200°C, specifically 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 200°C, etc., and of course other values within the above range, which are not limited here. When the drying temperature is low, the water content of the negative electrode material is high, resulting in a decrease in the first coulombic efficiency of the negative electrode material; when the drying temperature is high, the coating layer itself undergoes an excessive polycondensation reaction, the pore volume ratio of the negative electrode material in the range of 5nm to 35nm increases, the direct contact area between the solvated lithium ions and the graphite material increases, and the first efficiency of the negative electrode material decreases.
[0073] The present application controls the solid-liquid ratio, time and amount of coating material added during liquid phase coating, and can promote the polymer formed by the coating agent having active groups to be uniformly deposited and attached to the surface of graphite under stirring.
[0074] In a third aspect, an embodiment of the present invention further provides a battery, Figure 2 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 2 As shown, the battery includes a housing and an electrode assembly, and the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.
[0075] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active layer 102 disposed on at least one surface of the positive electrode current collector 101 .
[0076] In some embodiments, the positive electrode current collector 101 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer 102 includes a positive electrode active material, which includes a compound that can reversibly embed and de-embed metal ions.
[0077] In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel.
[0078] In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5O4) or at least one of lithium iron phosphate (LiFePO4).
[0079] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.
[0080] In some embodiments, the negative electrode current collector 201 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 202 includes a negative electrode material, which is the negative electrode material of the first aspect described above or the negative electrode material prepared by the above preparation method.
[0081] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0082] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0083] The embodiments in this patent are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other; in the following description, many specific details are explained to facilitate a full understanding of this application, and the described embodiments are only part of the embodiments of this application, not all of the embodiments. The embodiments of this application are further explained in multiple embodiments below.
[0084] Example 1
[0085] (1) 3 parts of vinyl sulfonic acid and pure water were mixed at a solid-liquid ratio of 1:100 to form a uniform organic coating solution, and 100 parts of graphite (average particle size of 17 μm) were added to form a uniform mixed solution.
[0086] (2) The mixed solution was subjected to polymerization reaction under stirring at a temperature of 60° C. for 1 hour; the pH value of the mixed solution was adjusted to 7 using a 0.5 mol / L sodium hydroxide solution (the molar ratio of vinyl sulfonic acid to sodium hydroxide was 1.0:1.05), and the mixed solution was heated to 90° C. and stirred until the solvent evaporated to form a powder state, and finally dried in a vacuum oven at 130° C. for 24 hours to obtain a negative electrode material.
[0087] Comparative Example 1
[0088] (1) 8 parts of vinyl sulfonic acid and pure water were mixed at a solid-liquid ratio of 1:40 to form a uniform organic coating solution, and 100 parts of graphite (average particle size of 17 μm) were added to form a uniform mixed solution.
[0089] (2) The mixed solution was subjected to polymerization reaction under stirring at a temperature of 60° C. for 1 hour; the pH value of the mixed solution was adjusted to 7 using a 0.5 mol / L sodium hydroxide solution (the molar ratio of vinyl sulfonic acid to sodium hydroxide was 1.0:1.05), and the mixed solution was heated to 90° C. and stirred until the solvent evaporated to form a powder state, and finally dried in a vacuum oven at 130° C. for 24 hours to obtain a negative electrode material.
[0090] Comparative Example 2
[0091] (1) 3 parts of vinyl sulfonic acid and pure water were mixed at a solid-liquid ratio of 1:100 to form a uniform organic coating solution, and 100 parts of graphite (average particle size of 17 μm) were added to form a uniform mixed solution.
[0092] (2) The mixed solution is subjected to a polymerization reaction under stirring at a temperature of 60° C. for 1 hour; the mixed solution is further heated to 90° C. and stirred until the solvent evaporates to form a powder state, and finally dried in a vacuum oven at 130° C. for 24 hours to obtain a negative electrode material.
[0093] According to the preparation steps of Example 1, Examples 2 to 18 (abbreviated as S1 to S18) and Comparative Examples (abbreviated as D1 to D4) were prepared. The process parameters of each Example and Comparative Example are specifically shown in Table 1:
[0094] Table 1. Preparation process parameters of negative electrode materials
[0095]
[0096]
[0097] Test Method
[0098] (1) Test methods for non-carbon elements and their contents in negative electrode materials:
[0099] Use an inductively coupled plasma emission spectrometer (ICP) to test the lithium, sodium, potassium, and aluminum elements in the negative electrode material; use an ion chromatograph to test the fluorine element in the negative electrode material; use a nitrogen and oxygen analyzer to test the nitrogen and oxygen elements in the negative electrode material; and use an infrared carbon-sulfur analyzer to test the sulfur element in the negative electrode material.
[0100] (2) Test method for particle size distribution of negative electrode materials: Use Malvern 3000 laser particle size analyzer to test the particle size volume distribution range of negative electrode materials. Put the dispersant (ethanol, pure water and low foaming surfactant) and the test sample in a 50mL beaker, add a certain amount of pure water, and stir with a glass rod to make the sample evenly dispersed. Set the equipment pump speed to 2400r / min~2500r / min and the frequency to 19.5Hz for particle size test.
[0101] (3) Test method for the tap density of negative electrode materials: Use a Microbe Tap Density Tester to test the specific surface area of the material. Place the negative electrode material in the sample chamber of the tap density tester, vibrate it 1000 times, and record the sample volume at this time. The tap density can be calculated according to the mass-to-volume ratio.
[0102] (4) Test method for specific surface area, pore size distribution and pore volume of negative electrode materials: Use a Microbeam tester to test the specific surface area of the material. Place the sample in a sample tube, use an isothermal jacket on the sample tube, place the filling rod in the bubble tube, install the retaining ring and O-ring on the bubble tube, and then place the assembled sample bubble tube into the corresponding analysis station for testing. Under constant temperature and low temperature, after measuring the adsorption amount of gas on the solid surface at different relative pressures, the sample monolayer adsorption amount is obtained based on the Brown-Ett-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area, pore volume and pore size distribution of the material.
[0103] (5) Test method for the surface morphology and coating layer of negative electrode material particles: Use a HITACHI-S4800 scanning electron microscope to observe the microscopic morphology of the surface of the negative electrode material. The steps are as follows: stick the conductive glue on the sample cup, evenly apply the sample on the conductive glue, use an ear-cleaning bulb to blow away the sample that is not firmly fixed, and put it into the scanning electron microscope room for testing. The test steps for the cross-section and coating layer are as follows: First, use a HITACHI-E3500 ion milling machine to polish the graphite particles, apply a small amount of carbon conductive glue on the edge of the sample table, and evenly sprinkle the graphite sample, press lightly with a glass sheet, wait for 2 minutes for the conductive glue to dry, and blow away the excess sample with an ear-cleaning bulb. Place the sample table on the sample holder and adjust the sample position. After completion, adjust the airflow to the maximum ion beam current and set the polishing time for sample processing. After completion, use a HITACHI-S4800 scanning electron microscope to observe the cross-section and coating layer on the surface of the negative electrode material.
[0104] (6) Raman test method for negative electrode materials: Use HORIBA-XPLORA laser confocal Raman spectrometer to test Raman scattering spectrum, laser wavelength 532nm. Take 30 points on the surface of negative electrode material particles for data collection, and then perform peak fitting on the scattering spectrum obtained at each point to obtain the peak at 1300cm -1 -1400cm -1The peak area of the characteristic peak D in the range of 1550cm -1 ~1600cm -1 The intensity ratio of the G characteristic peak in the range is I D / I G .
[0105] (7) Electrochemical performance test method: The negative electrode materials prepared in the examples and comparative examples were dissolved in deionized water at a mass ratio of 96.5:1.5:1 for the negative electrode material, carboxymethyl cellulose and styrene-butadiene rubber, respectively, and the solid content was controlled to be 50%. The negative electrode sheets were coated on copper foil current collectors and vacuum dried to obtain negative electrode sheets. Metal lithium sheets were used as counter electrodes and assembled into button cells in a glove box filled with argon. The charge and discharge tests were carried out at a current density of 0.1C with a charge and discharge interval of 0.01-1.5V. The first reversible specific capacity, first cycle charge capacity and first cycle discharge capacity were obtained by cyclic charge and discharge. The first coulomb efficiency = first cycle discharge capacity / first cycle charge capacity.
[0106] Table 2. Summary of performance test results of negative electrode materials
[0107]
[0108]
[0109] Table 3. Summary of battery performance test results
[0110]
[0111] like Figure 3a As shown, the surface morphology of the negative electrode material prepared in Example 1 is smooth, indicating that the coating layer is evenly distributed on the surface of the graphite material. Figure 3b As shown, under low-magnification field of view, the negative electrode material presents spherical particle distribution, and there are no coating agglomerates, indicating that the coating in the negative electrode material is difficult to nucleate independently, and there is almost no agglomeration of coating particles. Figure 4a The pore size distribution diagram of the negative electrode material in Example 1 in the range of 5nm to 35nm is shown. Figure 4b : is the total pore size distribution diagram. The pore volume of the material in Example 1 in the range of 5nm to 35nm accounts for 22.1%. It can be seen that the direct contact area between the negative electrode material and the solvated lithium ions in the electrolyte is small, the first lithium insertion irreversible reaction is weak, the interface stability of the negative electrode material is high, and the first coulombic efficiency and capacity of the negative electrode material are relatively excellent.
[0112] According to the test data of Examples 1 to 18, the total content of metal elements in the negative electrode material is within the range of 1300ppm-4400ppm. The presence of metal elements can enhance the conductivity within and / or between graphite particles, promote lithium ion interface transmission, and improve the first coulomb efficiency and cycle stability of the negative electrode material. At the same time, some metal elements can also form a composite similar to a metal-organic framework material with organic polymer materials. The inorganic-organic composite can be filled inside the graphite and / or attached to the surface of the graphite particles, and the volume proportion of pores with a pore size in the range of 5nm to 35nm in the total pore volume can be adjusted to 15% to 30%, which can effectively reduce the direct contact area between the solvated lithium ions and the graphite, reduce the irreversible side reactions between the negative electrode material and the electrolyte, and the solid-liquid contact interface of the negative electrode material is strong. The first cycle lithium removal capacity and the first coulomb efficiency of the negative electrode material are improved.
[0113] As shown in the data of Tables 1 to 3, according to the test data of Examples 1 to 5, in the process of mixing the coating agent, graphite and solvent to form a uniform organic coating solution, the pore volume proportion of the negative electrode material in the range of 5nm to 35nm can be effectively controlled by adjusting the solid-liquid ratio. As the solid-liquid ratio decreases, the content of the coating material per unit volume decreases, the deposition reaction on the surface of the graphite material becomes more uniform, the pore volume proportion in the range of 5nm to 35nm gradually decreases, and the graphite and the solvated Li + The direct contact area is reduced and the first coulombic efficiency of the negative electrode material is also improved.
[0114] According to the test data of Examples 1, 6 and 7, as the mass ratio of the coating material to graphite increases, the thickness of the coating layer on the surface of the graphite material increases, the pore volume proportion in the range of 5nm to 35nm decreases, the specific surface area of the negative electrode material also decreases, the first coulombic efficiency of the negative electrode material increases, but the capacity decreases.
[0115] According to the test data of Examples 1, 8 to 10, under the same process, changing the type of coating agent has no significant effect on the pore size distribution characteristics, specific surface area, first coulombic efficiency and other properties of the negative electrode material, indicating that the negative electrode materials prepared using the coating materials selected in this application can improve the specific surface area of the negative electrode material and improve the first coulombic efficiency of the negative electrode material.
[0116] According to the test data of Examples 1, 11 to 12, during the stirring reaction, solid-liquid separation and drying treatment, under the same process, changing the solvent type has no significant effect on the pore size distribution, specific surface area and first coulomb efficiency of the negative electrode material.
[0117] According to the test data of Example 1 and Examples 13 to 16, during the stirring reaction, solid-liquid separation and drying process, as the drying temperature increases, the specific surface area of the negative electrode material gradually increases, the pore volume ratio in the 5nm to 35nm range shows a trend of first decreasing and then increasing, and the first coulombic efficiency shows a trend of first increasing and then decreasing. This is because the decrease in the pore volume ratio will cause the solvated Li in the electrolyte to + The direct contact area with graphite is reduced, the irreversible reaction of the first lithium insertion is weak, and the first coulombic efficiency of the negative electrode material is improved. Properly increasing the drying temperature can improve the first coulombic efficiency of the negative electrode material; however, when the drying temperature is too high, due to excessive polycondensation of the coating layer on the surface of the graphite material, the pore volume ratio in the range of 5nm to 35nm increases, and the solvated Li in the electrolyte + The direct contact area with graphite increases, the irreversible reaction of the first lithium insertion intensifies, and the initial efficiency of the negative electrode material decreases.
[0118] According to the test data of Examples 1 and 17 to 18, under the same process, by changing the graphite type to microcrystalline graphite and artificial graphite, and selecting pH adjusters of other metal ions, as long as the total metal element content of the negative electrode material is controlled in the range of 1300ppm-4400ppm, and the volume proportion of pores with a pore diameter in the range of 5nm to 35nm in the total pore volume is in the range of 15% to 30%, the capacity and first efficiency of the negative electrode material can still be improved. It can be seen that the preparation method of the present application can be applied to different types of graphite negative electrode materials.
[0119] According to the test data of Comparative Example 1, the ratio of coating material to graphite material in the preparation process of Comparative Example 1 is 8:100. Due to the increase in the amount of coating material added, the coating layer on the surface of the negative electrode material is too thick, and the pore volume of the negative electrode material with a pore size in the range of 5nm to 35nm accounts for only 12.6%, and the pore volume ratio is too low. Since the amount of pH regulator added also increased year-on-year, the metal element content in the negative electrode material is as high as 5320ppm, and the inorganic-organic complex on the surface of the graphite material increases, which increases the specific surface area of the negative electrode material, intensifies the side reaction between the negative electrode material and the electrolyte, and reduces the first coulomb efficiency of the negative electrode material. At the same time, the pore volume ratio of the pore size in the range of 5nm to 35nm decreases, the direct contact area between the solvated lithium ions and the graphite in the electrolyte is too small, and the electrolyte is difficult to fully infiltrate the negative electrode material, resulting in the obstruction of lithium ion transmission and the obstruction of lithium ion transmission kinetics, which affects the capacity of the negative electrode material. According to the data in Table 4, compared with Example 3, the first-cycle lithium delithiation capacity of the negative electrode material in Comparative Example 1 is only 341 mAh / g, which is lower than the normal graphite-based negative electrode material requirement of 355 mAh / g, and the practicality of the negative electrode material is reduced.
[0120] Compared with Example 1, in the preparation process of Comparative Example 2, no pH regulator containing metal ions was added, resulting in a significant decrease in the mass content of metal elements in the negative electrode material, which is only 875 ppm. Although the volume proportion (21%) of pores with a pore size in the range of 5 nm to 35 nm in the negative electrode material in the total pore volume is in the range of 15% to 30%, the lithium ion transmission efficiency of the coating layer is greatly reduced, and the negative electrode material has processing performance problems in the process of preparing the electrode sheet, making it difficult to achieve mass production application.
[0121] Compared with Example 1, the drying temperature of Comparative Example 3 is higher during the preparation process, resulting in excessive condensation of the coating layer on the surface of the negative electrode material and an increase in the specific surface area of the negative electrode material. Although the mass content of the metal element of the negative electrode material (2060ppm) is in the range of 1300ppm to 4400ppm, and since the polymer coating layer has a higher degree of crystallinity as the drying temperature increases, the powder conductivity of the negative electrode material is slightly increased compared with Example 1; however, the coating layer after excessive condensation causes part of the pores to be re-exposed on the surface of the negative electrode material, the pore volume proportion of the negative electrode material with a pore diameter in the range of 5nm to 35nm is relatively high (31.5%), and the contact area between the solvated lithium ions in the electrolyte and the negative electrode material is too large, resulting in an aggravation of the irreversible side reaction of the first lithium insertion, excessive consumption of active lithium ions, and a decrease in the capacity and the first coulomb efficiency of the negative electrode material.
[0122] Compared with Example 1, Comparative Example 4 did not use a suitable coating material during the preparation process, which resulted in difficulty in forming a uniform coating layer on the surface of the graphite material. The mass content of metal elements in the negative electrode material reached 2061ppm. Under the action of a large amount of exposed graphite material and an appropriate amount of metal elements, the powder conductivity of the negative electrode material was relatively high. However, the exposed graphite material has more pores, and its pore volume in the range of 5nm to 35nm accounts for a relatively high proportion (37.2%). The contact area between the solvated lithium ions in the electrolyte and the negative electrode material is too large, resulting in an increase in the irreversible side reaction of the first lithium insertion, excessive consumption of active lithium ions, and a decrease in the capacity and the first coulomb efficiency of the negative electrode material.
[0123] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes graphite and an organic polymer material located on the surface and / or inside of the graphite; The negative electrode material comprises a metal element, wherein the metal element comprises at least one of lithium, sodium, potassium and aluminum; based on the total mass of the negative electrode material being 100%, the mass content of the metal element is 1300ppm to 4400ppm; The negative electrode material has pores, wherein the volume proportion of pores with a pore diameter ranging from 5 nm to 35 nm in the total pore volume is 15% to 30%.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: (1) The volume of pores with a pore diameter of less than 5 nm in the negative electrode material accounts for 2% to 10% of the total pore volume; (2) The volume proportion of pores with a pore diameter of 35 nm or more in the negative electrode material in the total pore volume is 60% to 83%; (3) The total pore volume of pores with a pore diameter of less than 250 nm in the negative electrode material is 0.005 cm 3 / g~0.02cm 3 / g.
3. The negative electrode material according to claim 1, characterized in that The organic polymer material located on the surface of the graphite forms a coating layer, and the thickness of the coating layer is 20nm-200nm.
4. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following characteristics: (1) The graphite includes at least one of artificial graphite, natural graphite and microcrystalline graphite; (2) The fixed carbon content of the graphite is ≥ 98%; (3) The negative electrode material contains a non-metallic element, and the non-metallic element includes at least one of nitrogen, sulfur, oxygen, boron and fluorine.
5. The negative electrode material according to claim 1, characterized in that The median particle size of the negative electrode material is 3 μm to 25 μm.
6. The negative electrode material according to any one of claims 1 to 5, characterized in that The powder conductivity of the negative electrode material is ≤1.35*10 under a pressure of 4kN 2 S / cm.
7. The negative electrode material according to any one of claims 1 to 5, characterized in that The specific surface area of the negative electrode material is 1.2 m 2 / g~3.7m 2 / g.
8. The negative electrode material according to any one of claims 1 to 5, characterized in that The tap density of the negative electrode material is 1.0 g / cm 3 ~1.3g / cm 3 .
9. The negative electrode material according to any one of claims 1 to 5, characterized in that In the Raman test spectrum of the negative electrode material, the negative electrode material has a peak at 1300 cm -1 -1400cm -1 There is a D peak at 1550cm -1 -1600cm -1 There is a G peak between them, and the Raman area ratio of the D peak to the G peak is I D / I G ≤0.
40.
10. A battery, characterized in that: The battery comprises the negative electrode material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium ion battery cathode composite material and preparation method thereof
CN101916846A
Preparation method of negative active material, negative active material and lithium ion battery
CN102376941A
Lithium ion battery negative electrode material, preparation method thereof and lithium ion battery
CN108666535A
Negative electrode material and preparation method thereof
CN114784252A
Lithium ion battery
CN116979017A
Cited By
Negative electrode material and battery
WO2025201568A1